PERAN IBU YANG BERHUBUNGAN DENGAN PENINGKATAN STATUS GIZI BALITA - Setiyowati Rahardjo; Siwi Pramatama Mars Wijayanti (Kesmas Indonesia, 2010)
ABSTRACT Family is the main and first development place of the children, and mother has an important role to take care them well. Most the malnutrition incidences in the children under five years old can be prevented if mother has enough knowledge about nutrient maintenance and food arrangement to their child. The kind of mother’s job also influences the nutrient status of their child. In 2007, undernutrition prevalence in Banyumas has reached 24,41% and 0,05% were identified as malnutrition. Public Health Center (PHC) II Sumbang is one of public health center that showed high incidence of lack of nutrient in child (55,95%). The aim of this research was to analyze the role of mother that influence the improvement of child’s nutrient status in PHC II Sumbang. The kind of this research was explanatory study with cross sectional method. Sample determined from child at coverage age 1 – 5 years old in village of Kotayasa,Banjarsari Kulon, Ciberem and Banjarsari Wetan with total amount has reached 100. Data analysis was used univariate,bivariate and multivariate. The result of this research showed that most of the children under five years old had a good nutrient status (86%). There were three important role of mother that influence nutrient status of their child. Identied mother’s roles were pattern of food preparation (p value = 0.003), pattern of health care (p value=0.041), and knowledge of nutrient (p value = 0.024). The most dominant role of mother that influence nutrient status of the child was pattern of food preparation. In order to improve knowledge of mother about nutrient status, health care and how to prepare good food to their child, health officials must give information to them regulary. This program can be included in Posyandu or PKK meeting. Key words : mother, nutritional status, underfive children Kesmasindo Volume 3, Nomor 1, Januari 2010, hlm. 56-65